2012
DOI: 10.1039/c2pp05385c
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen-bonding modulation of excited-state properties of flavins in a model of aqueous confined environment

Abstract: The singlet and triplet excited states properties of lumiflavin (LF), riboflavin (RF), flavin mononucleotide (FMN) and flavin adenine dinucleotide (FAD) in reversed micelles (RM) of sodium docusate (AOT) in n-hexane solutions were evaluated as a function of the water to surfactant molar ratio, w(0) = [H(2)O]/[AOT], by both steady-state and time-resolved absorption and fluorescence spectroscopy. The results indicated that hydrogen-bonding interactions between the isoalloxazine ring of the flavins with the water… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
45
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 44 publications
(50 citation statements)
references
References 49 publications
4
45
1
Order By: Relevance
“…The larger blue‐shift and narrower band of the cofactor fluorescence emission indicates that the isoalloxazine ring of FAD in WT Rc FPR (Figure 4 a) senses a much less polar environment than in the modified proteins and in bulk aqueous buffer 4. 15b Furthermore, both steady‐state and dynamic anisotropy data for WT Rc FPR are single‐fold larger than for the modified enzymes (Table 3), confirming that the isoalloxazine ring of FAD in the WT enzyme is more deeply buried than in the modified enzymes. This local rigidity of the isoalloxazine ring in the WT enzyme seems to be a key factor in maintaining its interaction with the Tyr66 residue, and hence induces an efficient quenching effect of 1 FAD* as discussed before.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The larger blue‐shift and narrower band of the cofactor fluorescence emission indicates that the isoalloxazine ring of FAD in WT Rc FPR (Figure 4 a) senses a much less polar environment than in the modified proteins and in bulk aqueous buffer 4. 15b Furthermore, both steady‐state and dynamic anisotropy data for WT Rc FPR are single‐fold larger than for the modified enzymes (Table 3), confirming that the isoalloxazine ring of FAD in the WT enzyme is more deeply buried than in the modified enzymes. This local rigidity of the isoalloxazine ring in the WT enzyme seems to be a key factor in maintaining its interaction with the Tyr66 residue, and hence induces an efficient quenching effect of 1 FAD* as discussed before.…”
Section: Discussionmentioning
confidence: 99%
“…Transient absorption signals of the excited triplet state of FAD ( 3 FAD*) in both air‐ and argon‐saturated buffer solutions were recorded at 710 nm with the m‐LFP 112 laser‐flash photolysis system (Luzchem Research Inc., Ottawa, Canada) using the third harmonic from a Minilite II (Continuum Inc., Santa Clara, CA) Nd‐YAG laser (355 nm, 7 ns full‐width at half‐maximum, FWHM, 5 mJ per pulse) as the excitation source 15b…”
Section: Methodsmentioning
confidence: 99%
“…For example, autofluorescence of flavins such as flavin adenine dinucleotide (FAD) have been long used to visualize metabolic changes in live samples and continues to be used as a “label-free imaging” option (Quinn et al , 2013; Jahn et al , 2015). This background could convolute fluorescent signals when using sensors at low expression levels, but at moderate sensor expression this is less likely because the lower extinction coefficient (~10,000 M −1 ·cm −1 ) and fluorescence quantum yield (< 0.01 to 0.06) of FAD (Valle et al , 2012). In order to mitigate problems with spectral overlap with FAD autofluorescence and to generate spectral diversity for multi-sensor imaging, Nakano et al .…”
Section: Methods For Detection and Imaging Atpmentioning
confidence: 99%
“…Steady‐state and time‐resolved techniques used in this work were fully described in previous reports …”
Section: Methodsmentioning
confidence: 99%
“…This fact, together with the photobiological relevance of flavin cofactors in blue‐light photoreceptors flavoproteins, invites to explore the nanoenvironmental control of the confined water on the photophysical and photochemical properties of flavins. Recently, we reported that the spectroscopic and singlet excited state properties of lumiflavin (LF), riboflavin (RF), flavin mononucleotide (FMN), and flavin adenine dinucleotide (FAD) (Scheme ) in Aerosol‐OT (AOT) RM dispersed in n ‐hexane were dominated by the capability of the water pool molecules to form hydrogen‐bonding interactions with the isoalloxazine ring …”
Section: Introductionmentioning
confidence: 99%